Effects of different fluid resuscitation regimes on lung injury and expression of pulmonary aquaporin 1 and aquaporin 5 in uncontrolled hemorrhagic shock in rats - Zhao, Wei-xian (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2009)
OBJECTIVE: To investigate the effects of different fluid resuscitation regimes on lung injury and expression of pulmonary aquaporin 1 (AQP1) and AQP5 in rats with uncontrolled hemorrhagic shock